The Conflict between Aristotle's Virtue and Modern Political Realism - Vranas, Vasilios (Conatus - Journal of Philosophy, 2018)
The political arena from the Renaissance to the dawn of the 21st century has become more demanding and complex, with positions such as Aristotle's virtue seeming utopian or outdated. The present paper attempts to examine whether Aristotelian virtue and bliss can be achieved in a century plagued by the economic crisis, terrorism, migration and the crisis of values.